Infrequência escolar e relação família-escola: perspectivas de professores, estudantes e mães/responsáveis - Elton César dos Santos (2019)
This study is based on two different views that coexist in the educational field: on the one hand, there have been a recurrent discourse among educational actors according to which working-class families are often negligent in relation to their children’s schooling; on the other hand, many studies from the sociology of education have argued that “parental neglect are a myth” (LAHIRE, 1997). Then, this thesis aims to understand the mutual implications between the phenomenon of school absenteeism and the relationship between working-class families and their children's schooling process, focusing on the discussion of the so-called “myth of parent omission”. In view of this, this master’s thesis aims to analyze the ways in which the relationships between families of working-class students and their respective educational institution. It is assumed that the cases of these students are useful situations to question the issue of parental neglect (or support), since not even the most basic condition of schooling - the student's presence in school - would be ensured. To understand better this situation, teachers, students and parents from a public school of Belo Horizonte – Minas Gerais – Brazil, located in a vulnerable and poor area were listened. The teachers were interviewed; focus group was run with students from 12 years-old to 16 years-old; finally, seven families of students that have school attendance problems were visited and interviewed. Data analysis indicates that, in their speeches, teachers interviewed express a certain understanding about the social reality of the student and how hard is for the most vulnerable families follow-up their children's school life. However, there persists among them, in a veiled way, the perception that some mothers or guardians do not give importance to the schooling process of their offspring. Focus group discussions suggest that, in the view of students, their families follow their school life, but they themselves use certain tricks to circumvent parental vigilance, demonstrating how the student's individual actions can interfere with the family-school relationship. Finally, the interviews conducted at home visits reveal that the cases of students with low school attendance studied can often be explained by factors related to the social conditions of the families; however, there are situations in which other variables need to be taken into consideration, whether related to the family – such as the quality of parental authority and the temporal dispositions –, the student – such as youth cultures – or the school system – absence of effective actions while combating student absenteeism. In this way, questions arise that allow problematizing the understanding that the parental neglect among working classes is a myth.